2021
DOI: 10.2196/31170
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps That Promote Emotion Regulation, Positive Mental Health, and Well-being in the General Population: Systematic Review and Meta-analysis

Abstract: Studies captured app usage or engagement data in a range of ways. Less than half of the total studies collected objective app usage data (e.g. time spent using the app or time spent using specific app

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 98 publications
2
64
0
Order By: Relevance
“…Various interventions to improve PMH exist in a variety of modalities, including individual, group and online formats, but targeting the general population (Bolier et al, 2013 ; Teixeira et al, 2019 ; Eisenstadt et al, 2021 ). However, no evidence-based intervention research on PMH in the psychotic disorder population has been found.…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions to improve PMH exist in a variety of modalities, including individual, group and online formats, but targeting the general population (Bolier et al, 2013 ; Teixeira et al, 2019 ; Eisenstadt et al, 2021 ). However, no evidence-based intervention research on PMH in the psychotic disorder population has been found.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion dysregulation is hypothesized to underpin a wide range of psychological difficulties [ 81 ]; in fact, transdiagnostic interventions, such as DBT or the Unified Protocol [ 82 ], focus on emotion dysregulation as the primary treatment target. Notably, however, emotion regulation is rarely included as an outcome variable in mobile mental health programs, despite its empirical and theoretical relevance to mental health and well-being [ 19 ]. In two studies of mHealth programs conducted with young adults [ 83 ] and homeless youth [ 84 ] that measured emotion regulation as an outcome variable, results showed no significant improvements in emotion regulation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should use causal methods to explore this further. In addition, the sample was primarily female, White, and highly educated, which is typical of studies of mobile mental health programs [ 19 ]. Future research should evaluate to what extent these results would generalize to other populations and actively recruit from hard-to-reach populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of commercially available mental health apps focus on whether the app increases well-being or decreases mental health symptoms [14,15]. However, researchers have yet to identify the emotional and cognitive processes by which mental health apps may influence wellbeing.…”
Section: Introductionmentioning
confidence: 99%